PENGURANGAN RISIKO BENCANA ALAM GEMPA BUMI SEBAGAI UPAYA UNTUK MELAKSANAKAN RISK-BASED EARLY WARNING - Pawirodikromo, Widodo (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2015)
The occurrence of natural hazards and disasters in general can not be avoided, and accordingly, the best way to overcome is to carry out an effective disaster management. The disaster management cycle has been defined and understood clearly.One of the main problem especially in the earthquake occurrence is the method of early warning. Semi quantitative investigation on the earthquake occurrences particularly at Yogyakarta province has been conducted. The relationship between earthquake occurrence and an effective early warning became the main discussion. The data of earthquake occurrence at Yogyakarta provinve in general is still relatively limited. The only available data was started at 1960’s and therefore for the purpose of earthquake forecasting and prediction, the numbers/completeness of the data should be improved. Result of the investigation showed that the concept of early warning system will be more comprehensive if it be conducted by using the principle of Risk-Based Early Warning. Reducing the disaster fatalities can be done not only by carrying out an early warning immediately before hazard but also can be extended inclusively in the disaster risk reduction program. Based on preliminary investigation and experiences, the structural damage at Yogukarata province would be occur if the shallow earthquake magnitude M is greater than 5.3 with the epicenter distance approximately less than 40 km. There are several earthquake prediction methods that have been developed by researchers, and one of them is strange animal behavior before earthquake. The strange animal behaviors were occurred before the Yogyakarta 27 May 2006 earthquake. This method can be used for the earthquake early warning in the future when it has been verified successfully.